Müllerian Mimicry as a Result of Codivergence between Velvet Ants and Spider Wasps - Rodriguez, Juanita; Pitts, James P.; von Dohlen, Carol D.; Wilson, Joseph S. (PLOS ONE, 2014)
Recent studies have delineated a large Nearctic Müllerian mimicry complex in Dasymutilla velvet ants. Psorthaspis spider wasps live in areas where this mimicry complex is found and are phenotypically similar to Dasymutilla. We tested the idea that Psorthaspis spider wasps are participating in the Dasymutilla mimicry complex and that they codiverged with Dasymutilla. We performed morphometric analyses and human perception tests, and tabulated distributional records to determine the fit of Psorthaspis to the Dasymutilla mimicry complex. We inferred a dated phylogeny using nuclear molecular markers (28S, elongation factor 1-alpha, long-wavelength rhodopsin and wingless) for Psorthaspis species and compared it to a dated phylogeny of Dasymutilla. We tested for codivergence between the two groups using two statistical analyses. Our results show that Psorthaspis spider wasps are morphologically similar to the Dasymutilla mimicry rings. In addition, our tests indicate that Psorthaspis and Dasymutilla codiverged to produce similar color patterns. This study expands the breadth of the Dasymutilla Müllerian mimicry complex and provides insights about how codivergence influenced the evolution of mimicry in these groups.